Graphene super-hydrophobic anticorrosive composite coating as well as preparation method and application thereof
By using the combination of dopamine hydrochloride and fluorosilane in the graphene coating, a graphene superhydrophobic anti-corrosion composite coating was prepared, which solved the problem of 'corrosion promoting activity' of graphene coating and achieved better metal anti-corrosion Performance and simplify the preparation process.
Patent Information
- Application Number
- CN202411775986.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The graphene coating has a problem of 'corrosion promoting activity', which leads to its poor effectiveness in protecting metals for a long time. At the same time, the existing anticorrosion composite coating preparation process is complex.
By sonicating the graphene material with dopamine hydrochloride in a weak alkali environment, combining the load of fluorosilane and crosslinking of PDMS, a graphene superhydrophobic anti-corrosion composite coating was prepared to inhibit the 'corrosion and promotion of activity' of graphene' And improve corrosion resistance.
This coating can effectively inhibit the 'corrosion-promoting activity' of graphene, significantly improve the anti-corrosion performance of metals, and is simple in preparation and low in cost.
Smart Images

Figure CN119410263A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of metal corrosion protection, and in particular relates to a graphene super-hydrophobic anti-corrosion composite coating and a preparation method and application thereof. Background Art
[0002] Metal corrosion is a very common electrochemical behavior. Because it destroys the durability and permanence of products and causes premature failure of metal parts, resulting in economic losses, improving the anti-corrosion performance of metals is particularly important for metal infrastructure such as bridges and ships. At present, how to enhance the anti-corrosion performance of metals is still a difficult problem that needs to be solved urgently.
[0003] Common measures to protect metals include cathodic protection, electrodeposition, and coating protection. Among them, coating protection is one of the most effective methods due to its strong anti-corrosion performance, low cost, and simple preparation process. It is usually divided into inorganic, organic, and organic-inorganic hybrid coatings. Inorganic coatings can be prepared by methods such as electrodeposition, and exhibit good properties such as high temperature resistance, but their practical applications are often limited by poor mechanical properties. Organic coatings have good wear resistance, but solvent volatilization during the preparation process may cause shrinkage, fracture, and defects inside the coating, and cannot maintain long-term protection for the metal substrate. In order to improve the overall performance, micro-nanostructured inorganic particles are often mixed with an organic polymer matrix in the form of a filler to prepare an organic-inorganic hybrid composite coating, which can take into account the advantages of both inorganic and organic coatings.
[0004] In recent years, two-dimensional inorganic fillers such as graphene, boron nitride (BN), zirconium phosphate (ZrP), and molybdenum disulfide (MoS2) have attracted widespread attention because of their good barrier properties. Filling in organic coatings can extend the penetration path of corrosive media and produce a "maze" effect. Among them, graphene stands out due to its high specific surface area, good chemical stability, and excellent barrier properties. However, graphene has a more positive electrode potential than metals such as copper. Once the coating is damaged, the graphene at the cathode and the metal at the anode will form galvanic corrosion. The high conductivity of graphene will further accelerate the corrosion activity of the metal. Therefore, the "corrosion-promoting activity" problem of graphene coatings reduces the effectiveness of long-term protection of metals.
[0005] Most of the existing anti-corrosion composite coatings ignore the "corrosion-promoting activity" problem of graphene coatings, and the preparation process of anti-corrosion coatings is complicated. The Chinese invention patent with publication number CN 113789109 A suppresses the "corrosion-promoting activity" by doping boron atoms and fluorine atoms, and the prepared coating has antibacterial and anti-corrosion properties. However, in the process of heteroatom doping, corrosive substances may be introduced to cause lattice defects, and the conductivity of graphene may be increased, which in turn aggravates corrosion. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a graphene super-hydrophobic anti-corrosion composite coating that can inhibit the "corrosion promoting activity" of graphene, as well as a preparation method and application thereof.
[0007] In order to solve the above technical problems, the technical solution proposed by the present invention is:
[0008] A method for preparing a graphene super-hydrophobic anti-corrosion composite coating comprises the following steps:
[0009] S1. dissolving the graphene material and dopamine hydrochloride in water and performing ultrasonic treatment in a weak alkaline environment;
[0010] S2. dissolving fluorosilane in ethanol and adding it to the solution after ultrasonication in S1, stirring continuously at a first temperature, then heating to a second temperature, continuing stirring, and then cooling, filtering, and drying to obtain a composite filler;
[0011] S3. The composite filler obtained in S2 is ultrasonically dispersed in a solvent, PDMS and a curing agent are added and stirred, and a coating is obtained after ultrasonication;
[0012] S4. Apply the coating prepared in S3 to the surface of the metal substrate and cure it to obtain a graphene super-hydrophobic anti-corrosion composite coating.
[0013] As a further improvement, the graphene-based material in S1 is one of graphene, graphene oxide, or reduced graphene oxide.
[0014] As a further improvement, the mass ratio of the graphene material to dopamine hydrochloride in S1 is 0.5 to 12.5:1.
[0015] As a further improvement, the pH of the weak alkaline environment in S1 is 8.0 to 8.8; and the ultrasonic treatment time is 0.5 h to 2.0 h.
[0016] As a further improvement, the fluorosilane in S2 is one or any combination of heptadecafluorodecyltrimethoxysilane, heptadecafluorodecyltriethoxysilane, tridecafluorooctyltrimethoxysilane, or tridecafluorooctyltriethoxysilane.
[0017] As a further improvement, the mass ratio of the fluorosilane to dopamine hydrochloride is 1.25-5:1.
[0018] As a further improvement, in S2, the first temperature is 25-40° C., the second temperature is 60-90° C., and the stirring time at the first temperature and the stirring time at the second temperature are both 11-14 hours.
[0019] As a further improvement, the mass ratio of PDMS to the composite filler in S3 is 5 to 10:1.
[0020] The present invention also provides a graphene super-hydrophobic anti-corrosion composite coating, which is prepared by the preparation method, wherein the graphene material is loaded with fluorosilane nanoparticles by using polydopamine as an adhesive.
[0021] The present invention also provides an application of the graphene super-hydrophobic anti-corrosion composite coating in metal corrosion protection.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] In order to suppress the "corrosion-promoting activity" of graphene coating, the present invention uses polydopamine as an adhesive and loads fluorosilane to insulate and passivate graphene, thereby blocking the electron transmission between graphene and the metal substrate, alleviating the problem of graphene's "corrosion-promoting activity". At the same time, a super-hydrophobic composite coating is prepared by modification with fluorosilane, and the non-stickiness and non-wettability of the super-hydrophobic surface are used to reduce the contact between the corrosive medium and the coating, further improving the anti-corrosion performance.
[0024] The present invention utilizes dopamine to form polydopamine by self-oxidative polymerization under alkaline conditions, and grafts it onto graphene. The rich functional groups of polydopamine can not only covalently modify graphene, but also reduce the aggregation tendency of graphene-type fillers in the organic polymer matrix, improve the compatibility of fillers with PDMS, facilitate better dispersion of fillers in PDMS, and prepare a uniform coating, thereby further improving the anti-corrosion performance. In addition, polydopamine can be used as an adhesive to provide a large number of "anchoring points" for the loading of fluorosilane, promote the loading of fluorosilane, and thus achieve insulating passivation of graphene.
[0025] Therefore, the present invention simultaneously utilizes fluorosilane to perform super-hydrophobic modification and insulating passivation on graphene oxide, and acts synergistically with polydopamine to improve the anti-corrosion performance.
[0026] The present invention prepares a composite filler GDF by mixing a graphene oxide (GO) dispersion, dopamine hydrochloride (DA) and fluorosilane through a simple one-pot method to complete the modification. The prepared composite filler is then mixed with polydimethylsiloxane (PDMS), a curing agent is added and mixed, and then high-temperature curing is performed to cross-link the silicone resin and the filler to obtain a composite coating GDF / PDMS. The present invention utilizes organic-inorganic hybridization to prepare a composite coating, and the composite filler can be obtained by mixing in one step, and the preparation process is simple and the preparation cost is low.
[0027] The composite coating prepared by the present invention can inhibit the "corrosion-promoting activity" of graphene, has excellent corrosion inhibition performance, and can achieve super-hydrophobicity by cross-linking with PDMS having low surface energy, and has excellent self-cleaning performance. It has good application value in the field of metal corrosion protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 is the FT-IR graph of the composite filler GDF;
[0030] Figure 2 is the SEM image of the composite filler GDF;
[0031] Figure 3 These are optical photographs of the GDF / PDMS coating (a) immersed in cola, (b) immersed in coffee, and (c) self-cleaning performance process. Numbers 1, 2, and 3 represent the time points in chronological order.
[0032] Figure 4 It is the modulus value diagram of composite coating and bare copper sheet;
[0033] Figure 5 It is the potentiodynamic polarization curve of the composite coating and the bare copper sheet;
[0034] Figure 6 It is the modulus value diagram of the scratch-treated composite coating and bare copper sheet. DETAILED DESCRIPTION
[0035] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0036] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0037] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0038] In some specific embodiments, the method for preparing the graphene super-hydrophobic anti-corrosion composite coating of the present invention comprises the following steps:
[0039] S1. Mix and dissolve graphene material and dopamine hydrochloride (DA) in water, and perform ultrasonic treatment in a weak alkaline environment.
[0040] Preferably, the graphene-based material may be one of graphene, graphene oxide, and reduced graphene oxide.
[0041] Preferably, the mass ratio of graphene oxide to dopamine hydrochloride is 0.5-12.5:1, more preferably 0.5-2.5:1, further preferably 0.5-1:1, and most preferably 0.5:1.
[0042] Preferably, the weak alkaline environment can be achieved by adding ammonia water, the pH is controlled at 8.0 to 8.8, preferably 8.5, and the dosage can be 0.05 to 0.15 g / 200 mL (mass of ammonia water / volume of water).
[0043] Preferably, the ultrasonic time may be 0.5 h to 2.0 h.
[0044] S2. Dissolve fluorosilane in ethanol and add it to the solution after ultrasonic treatment in S1, and continue stirring the system at the first temperature, then raise the temperature to the second temperature and continue stirring. Cool, filter and dry to obtain the composite filler GDF.
[0045] Preferably, the fluorosilane can be one of heptadecafluorodecyltrimethoxysilane, heptadecafluorodecyltriethoxysilane, tridecafluorooctyltrimethoxysilane and tridecafluorooctyltriethoxysilane. The dosage (mass ratio of fluorosilane to dopamine hydrochloride) can be 1.25 to 5:1.
[0046] Preferably, the amount of ethanol used may be 30-50 mL / 1.5 g fluorosilane.
[0047] Preferably, the first temperature may be 25-40° C., and the second temperature may be 60-90° C. Stirring at low temperature allows dopamine to self-polymerize to form polydopamine, which is then loaded on graphene, and increasing the temperature accelerates the reaction rate.
[0048] Preferably, the two stirring times (stirring at the first temperature and stirring at the second temperature) can both be 11-14 hours.
[0049] Preferably, after cooling and filtering, the mixture is washed with ethanol and dried. The drying temperature may be 80-100° C. and the drying time may be 12-24 hours.
[0050] S3. Ultrasonic dispersion of the composite filler obtained in S2 in a solvent (eg, methanol), followed by addition of polymer PDMS (polydimethylsiloxane), stirring, and then adding a curing agent and continuing to stir, followed by another ultrasonic dispersion to obtain a coating.
[0051] Preferably, the mass ratio of the PDMS to the composite filler can be 5 to 10:1. The mass ratio of PDMS to the curing agent is preferably 10:1. The PDMS in the following embodiments is Dow Corning 184PDMS (Sylgard 184A). The curing agent in the following embodiments is Sylgard 184B, the B component of Dow Corning 184PDMS.
[0052] Preferably, the ultrasonic dispersion is carried out in methanol, and the ultrasonic time can be 0.5-2.0 hours. The stirring time after adding PDMS can be 1-3 hours. The stirring time after adding the curing agent can be 5-30 minutes.
[0053] S4. Apply the coating prepared in S3 to the surface of the metal substrate and cure it to obtain a composite coating.
[0054] Preferably, the metal substrate is pretreated first, and the pretreatment method is: polishing with sandpaper, and ultrasonic cleaning with deionized water and anhydrous ethanol in sequence.
[0055] Preferably, the coating method may be spray coating or drip coating.
[0056] Preferably, the curing temperature may be 120-170° C., and the curing time may be 15-60 min.
[0057] Example 1
[0058] Super hydrophobic composite coating G 0.2 Preparation method of DF / PDMS:
[0059] 1.1 Dissolve 0.2g of graphene oxide, 0.4g of dopamine hydrochloride and 0.1g of ammonia water in 200mL of deionized water (pH=8.5) and ultrasonicate for 1h. Then dissolve 1.5g of fluorosilane (1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane) in 40mL of ethanol solution and add it to the ultrasonicated solution. The system was continuously magnetically stirred in a 40℃ oil bath for 12h. Then the temperature was raised to 70℃ and magnetic stirring was continued for 12h. After the system was cooled to room temperature, vacuum filtration was performed, and the filter cake was washed with ethanol and dried to obtain the composite filler GDF.
[0060] 1.2 Polish the copper sheet with 400 mesh, 800 mesh, 1000 mesh, 1500 mesh and 2000 mesh metallographic sandpaper in turn, clean the copper sheet with deionized water and anhydrous ethanol for 10 minutes respectively, blow dry and set aside.
[0061] 1.3 Weigh 0.05 g of the composite filler prepared in 1.1 and disperse it in 15 mL of methanol, and evenly disperse it by ultrasonication for 1 hour. Then add 0.50 g of PDMS, stir at room temperature for 1 hour, add 0.05 g of curing agent and stir for 5 minutes. Finally, ultrasonicate for 30 minutes to obtain the coating.
[0062] 1.4 Spray the coating obtained in 1.3 onto the surface of the copper sheet treated in 1.2, adjust the spray gun to a smaller spray volume, and keep it about 5 cm away from the copper sheet. Curing at high temperature (160°C) for 15 minutes.
[0063] Figure 1 This is the FT-IR image of the composite filler GDF. The composite filler GDF is at 3423cm -1 There is a broad absorption peak at 1145cm, which is a typical hydroxyl absorption peak (including hydroxyl stretching vibration in water); -1 The absorption peak at 1614cm is caused by CC stretching vibration. -1 A strong absorption peak appears at 1513cm, which can be attributed to the stretching vibration of C=C, CN and the bending vibration of CH; -1 The absorption peak at 459cm should be attributed to NH bending vibration, which fully verifies that polydopamine is successfully loaded on graphene oxide. -1 、809cm -1 There is an absorption peak at 1205cm, which is caused by Si-O-Si bending vibration and symmetrical stretching vibration respectively. -1 A strong absorption peak appears at , which can be attributed to the CF stretching vibration, indicating that fluorosilane has been successfully loaded on the surface of graphene oxide.
[0064] Figure 2 It is the SEM image of the composite filler GDF, which shows that due to the effect of polydopamine adhesive, multiple fluorosilane (FS) nanoparticles with low surface energy are loaded on the graphene oxide (GO) sheet, and the smooth graphene oxide sheet becomes rougher.
[0065] Example 2
[0066] Same as Example 1, except that 0.2g of graphene oxide was replaced with 1.0g, and the prepared coating was G 1.0 DF / PDMS.
[0067] Example 3
[0068] Same as Example 1, except that 0.2 g of graphene oxide was replaced with 5.0 g, and the prepared coating was G 5.0 DF / PDMS.
[0069] Example 4
[0070] The same as Example 1, except that the prepared composite coating is scratched, that is, a 2 mm long scratch is artificially created.
[0071] Example 5
[0072] The same as Example 2, except that the prepared composite coating is scratched, that is, a 2 mm long scratch is artificially created.
[0073] Example 6
[0074] The same as Example 3, except that the prepared composite coating is scratched, that is, a 2 mm long scratch is artificially created.
[0075] Comparative Example 1
[0076] Composite coating without fluorosilane superhydrophobic modification:
[0077] The only difference from Example 1 is that fluorosilane and ethanol are not added in 1.1, and the prepared coating is G 0.2 D / PDMS.
[0078] Comparative Example 2
[0079] Bare copper sheet:
[0080] Same as step 1.2 in Example 1.
[0081] Comparative Example 3
[0082] The only difference from Example 1 is that dopamine hydrochloride and ammonia water are not added in step 1.1. Step 1.1 Fluorosilane is difficult to load.
[0083] Results Test Analysis
[0084] 1. Contact angle test
[0085] Equipment: Contact angle measuring instrument
[0086] Conditions: Use a syringe or pipette to control the volume of the wetting liquid to 10 μL.
[0087] The contact angle of the GDF / PDMS coating in Example 1 is 151.5°±0.5°.
[0088] 2. Sliding angle test
[0089] Equipment: Build a simple inclined table to allow water droplets to slide on the coating surface. Use a protractor to measure the inclination angle of the coating when the water droplet can slide, which is the sliding angle of the coating.
[0090] Conditions: Use a syringe or pipette to control the volume of the wetting liquid to 10 μL.
[0091] The sliding angle of the GDF / PDMS coating in Example 1 is 7.9°±0.1°.
[0092] The water contact angle of the coating is 151.5°±0.5°, and the sliding angle is 7.9°±0.1°, indicating that the coating is superhydrophobic.
[0093] 3. Self-cleaning performance test
[0094] like Figure 3 After the super hydrophobic coating GDF / PDMS of Example 1 was immersed in cola and coffee respectively, no substance remained on the surface of the coating, indicating that the coating has excellent antifouling performance. The sediment on the surface of the GDF / PDMS coating was washed with water, and the sediment on the surface of the coating could be quickly taken away by the water, and no drop of water was left along the path where the sediment moved, indicating that the coating has excellent self-cleaning performance.
[0095] 4. Electrochemical testing
[0096] Equipment: Shanghai Chenhua CHI760E
[0097] Conditions: The test was carried out under a traditional three-electrode system: a saturated calomel electrode was used as the reference electrode, a platinum electrode was used as the counter electrode, the coatings of the above-mentioned embodiments and comparative examples were used as the working electrodes and the working area was 1cm×1cm. Using 3.5wt% sodium chloride as the corrosion medium, the alternating current impedance (EIS) and potentiodynamic polarization curve of the coating were tested. The parameters of the alternating current impedance were set as follows: the initial frequency was 100000Hz, the end frequency was 0.01Hz, and the sinusoidal signal AC amplitude was 20mV. Before the test, each coating was immersed in 3.5wt% sodium chloride for 15 minutes, and the test was started after the open circuit voltage stabilized. The potentiodynamic polarization curve was scanned in the range of -350mV to -180mV, and the scanning speed was 0.5mV·s -1 The EIS test data was fitted by establishing an equivalent circuit using ZSimpWin software.
[0098] The corrosion inhibition efficiency of the prepared GDF / PDMS coating is 96.07% (see Figure 5 ), the low-frequency impedance is increased by an order of magnitude compared to the bare copper sheet (see Figure 4 ). and the scratch-treated coatings showed an inhibitory effect on "corrosion promoting activity" (see Figure 6 ).
[0099] Figure 4 This is the modulus diagram of the composite coating and bare copper sheet. Low frequency impedance modulus (|Z| 0.01 ) is higher, indicating that the coating has better anti-corrosion performance. The |Z| 0.01 The highest. From the modulus value diagram, it can be clearly seen that the |Z| 0.01 is lower than that of each coating. It can be seen that GDF / PDMS can improve the corrosion inhibition performance of copper metal substrate. And the |Z| 0.01 It is lower than that in the example, indicating that the modification of fluorosilane is beneficial to improving the anti-corrosion performance of the coating.
[0100] Figure 5 It is the potentiodynamic polarization curve of the composite coating and the bare copper sheet. The more positive the corrosion potential, the less likely the coating is to corrode; the smaller the corrosion current density, the slower the corrosion rate of the coating. Compared with Comparative Example 2 (bare copper sheet), the corrosion potential of the embodiment (GDF / PDMS coating) moves in the positive direction successively (the effect of embodiment 1 is better than that of embodiment 2, and embodiment 2 is better than that of embodiment 3). And the corrosion current density moves in a more negative direction successively. The tendency to corrode gradually decreases. The GDF / PDMS coating has a smaller corrosion rate and better corrosion resistance.
[0101] Table 1 lists the corrosion potential and corrosion current density of each coating. It can be seen that Comparative Example 1 has a more positive corrosion potential and a lower corrosion current density than Comparative Example 2, which shows that dopamine is beneficial to the improvement of anti-corrosion performance. At the same time, the embodiment has better performance than the comparative example, indicating that the loading of fluorosilane improves the anti-corrosion performance of the coating.
[0102] Table 1
[0103]
[0104] EIS tests and potentiodynamic polarization curve tests were performed on coatings with different filler contents and bare copper sheets. The composite coatings of the embodiments all had good anti-corrosion properties. 0.2 DF / PDMS has the highest low-frequency impedance modulus, which is an order of magnitude higher than that of bare copper sheet, and has a lower corrosion current density and more positive corrosion potential, showing the best anti-corrosion performance.
[0105] Figure 6 The scratched GDF / PDMS coatings (Examples 4 to 6) still have higher low-frequency impedance modulus (|Z|) than the comparative example 2 (bare copper sheet). 0.01 ), the coating still has the ability to protect the bare copper sheet, indicating that the “corrosion-promoting activity” of graphene can be suppressed.
[0106] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Therefore, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the scope of protection of the technical solution of the present invention.
Claims
1. A method for preparing a graphene super-hydrophobic anti-corrosion composite coating, characterized in that: The steps include: S1. dissolving the graphene material and dopamine hydrochloride in water and performing ultrasonic treatment in a weak alkaline environment; S2. dissolving fluorosilane in ethanol and adding it to the solution after ultrasonication in S1, stirring continuously at a first temperature, then heating to a second temperature, continuing stirring, and then cooling, filtering, and drying to obtain a composite filler; S3. The composite filler obtained in S2 is ultrasonically dispersed in a solvent, PDMS and a curing agent are added and stirred, and a coating is obtained after ultrasonication; S4. Apply the coating prepared in S3 to the surface of the metal substrate and cure it to obtain a graphene super-hydrophobic anti-corrosion composite coating.
2. The preparation method according to claim 1, characterized in that: The graphene-based material in S1 is one of graphene, graphene oxide, or reduced graphene oxide.
3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the graphene material to dopamine hydrochloride in S1 is 0.5 to 12.5:
1.
4. The preparation method according to claim 1 or 2, characterized in that: The pH of the weak alkaline environment in S1 is 8.0 to 8.8; and the ultrasonic treatment time is 0.5 h to 2.0 h.
5. The preparation method according to claim 1, characterized in that: The fluorosilane described in S2 is one or any combination of heptadecafluorodecyltrimethoxysilane, heptadecafluorodecyltriethoxysilane, tridecafluorooctyltrimethoxysilane, or tridecafluorooctyltriethoxysilane.
6. The preparation method according to claim 1 or 5, characterized in that: The mass ratio of the fluorosilane to dopamine hydrochloride is 1.25-5:
1.
7. The preparation method according to claim 1 or 5, characterized in that: In S2, the first temperature is 25-40°C, the second temperature is 60-90°C, and the stirring time at the first temperature and the stirring time at the second temperature are both 11-14 hours.
8. The preparation method according to claim 1, characterized in that: The mass ratio of PDMS to the composite filler in S3 is 5 to 10:
1.
9. A graphene super-hydrophobic anti-corrosion composite coating, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 8, wherein the graphene material is loaded with fluorosilane nanoparticles by using polydopamine as a binder.
10. Use of the graphene super-hydrophobic anti-corrosion composite coating according to claim 9 in metal corrosion protection.
Citation Information
Patent Citations
Fluorine and boron double-doped graphene / alkyd resin composite coating and preparation method thereof
CN113789109A
Articles comprising durable water repellent, icephobic and / or biocidal coatings
CA3087026A1
Super-hydrophobic conductive anticorrosive graphene coating and preparation method thereof
CN111234696A
Preparation method and application of modified anti-corrosion super-hydrophobic integrated coating
CN112300697A
Cationic dopamine functionalized graphene water-based anti-corrosive paint as well as preparation method and application thereof
CN113122044A